2005
DOI: 10.1179/oeh.2005.11.2.185
|View full text |Cite
|
Sign up to set email alerts
|

A Global Survey of Occupational Health Competencies and Curriculum

Abstract: The World Health Organization has identified a worldwide shortage of occupational health professionals, but evidence suggests that the work and education of these professionals vary across countries. This survey examined the professional development of occupational physicians, occupational nurses, industrial hygienists, and ergonomists in terms of practice competencies and academic curriculum. Of 89 countries that received the survey, 48 (54%) responded. Important differences in competencies and curricula were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 22 publications
1
29
0
6
Order By: Relevance
“…Substantial differences in required competency sets for OPs and OHNs were observed in a global survey on work jurisdiction of OH professionals undertaken over a decade ago 7 . Our contrasting, more highly correlated findings may be explained by OH practice evolution already described and service provision/multidisciplinary models currently in place.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Substantial differences in required competency sets for OPs and OHNs were observed in a global survey on work jurisdiction of OH professionals undertaken over a decade ago 7 . Our contrasting, more highly correlated findings may be explained by OH practice evolution already described and service provision/multidisciplinary models currently in place.…”
Section: Discussionmentioning
confidence: 64%
“…This is important for clinical governance and identifying ongoing training requirements. OP and OHN competency requirements separately have been studied in various countries, 3–9 but little research has made direct comparisons between these two professional groups 7 . A global survey comparing work jurisdiction of OH professionals demonstrated substantial differences for OPs and OHNs in required competency sets, although this was undertaken over a decade ago 7 …”
Section: Introductionmentioning
confidence: 99%
“…The low response rate can be considered a study limitation and it is possible that these results may not be representative of all UK OHNs. Other Internet-based surveys and competency studies have also demonstrated low response rates [15,30]. From an OHN perspective, there have been recent concerns about a lack of engagement and direction within the discipline [6], which may explain this response rate.…”
Section: Discussionmentioning
confidence: 99%
“…OH practice is constantly evolving and OHNs have to develop continuously and adapt competencies based upon core skills, resulting in OH nursing becoming a mix of ‘traditional’ and ‘emergent’ functions [14]. OHN roles and competencies have been the subject of research [15–23]. Two Australian studies [20,23] identified that OHNs were not engaging fully in all practice areas defined in their competency standards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation